(untitled) (Research, Society and Development, 2020)
The process of beneficiation of minerals generates as a byproduct the tailings, usually disposed in containment dams, which may have a high potential associated risk, causing significant environmental impacts when these structures rupture. Therefore, in 2010, the National Dam Safety Policy was created, which has as one of its instruments the Mining Dams Emergency Action Plan (PAEBM). In the municipality of Itabira (MG) there is an important mining complex, where part of the waste generated during the processing of iron ore is deposited in the Itabiruçu Dam. Thus, this research aimed to examine the PAEBM of this structure, characterizing the flood spot resulting from its possible disruption, and analyze the likely impacts on land use and occupation. For this, the documentary research was used, based on satellite image analysis, the Itabiruçu Dam PAEBM and the map containing the flood spot. With these data, it was possible to identify that the stain resulting from a possible dam rupture would occupy an area of 8.9 km2 of the municipality, including along its route 13.2% of the urban perimeter and 67.6% of the pasture areas, thus causing both environmental and socioeconomic impacts. In addition, it was found that the implemented warning system did not reach in all respects the decibels required by legislation. Thus, it is recommended the development of new research directed to the creation of more efficient alerting techniques and the elimination or minimization of the impacts resulting from an eventual disruption.